Towards Headship: Developing Leadership and Management Skills in an Italian University Master Course - Giovanna Barzanò; Giovanni Moretti (LED Edizioni Universitarie, 2015)
This article reports on an exploratory qualitative study undertaken with the students of the tenth edition of the «Leadership and Management in Education Master Course» (LMEMC) held in Italy by the Department of Education of the University Roma Tre and attended by educational professionals from Greece and Italy, in prevalence aspiring to career improvement and new leadership roles. The study is part of an in-depth self-evaluation process aimed at updating the course activities and exploring professional adult learning. Our data consists of 65 written interviews, undertaken with student-teachers and focusing on their motivations and their positive and negative expectations towards leadership roles. After referring to the international debate on leadership preparation and development, we situate the LMEMC looking at: (a) the context of Italian HE postgraduate studies; (b) the context of educational leadership preparation and development in Italy and in Greece; (c) the course design and delivery strategies. We then describe the methodologies and research tools employed and draw from our results some hints for possible new developments in the LMEMC and in leadership preparation activities. Our data also allows us to reflect on the benefits of sustainable self-evaluation processes of adult learning activities.